2017
DOI: 10.1038/s41598-017-07612-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel giardicidal compounds bearing proton pump inhibitor scaffold proceeding through triosephosphate isomerase inactivation

Abstract: Giardiasis is a worldwide parasitic disease that affects mainly children and immunosuppressed people. Side effects and the emergence of resistance over current used drugs make imperative looking for new antiparasitics through discovering of new biological targets and designing of novel drugs. Recently, it has determined that gastric proton-pump inhibitors (PPI) have anti-giardiasic activity. The glycolytic enzyme, triosephosphate isomerase (GlTIM), is one of its potential targets. Therefore, we employed the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 42 publications
7
37
1
Order By: Relevance
“…In this study, we can relate the importance of loop 6 and loop 7 in the development of drugs against TcTIM and GlTIM, and we propose than, our important amino acids are in the loop 3 region, which alter the region of the interface and C4 has a greater effect with the loop 7, resulting in the alteration of the conformational structure of the active site or that some conformation interacts with Lys14 or His97 that decreases glycolytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we can relate the importance of loop 6 and loop 7 in the development of drugs against TcTIM and GlTIM, and we propose than, our important amino acids are in the loop 3 region, which alter the region of the interface and C4 has a greater effect with the loop 7, resulting in the alteration of the conformational structure of the active site or that some conformation interacts with Lys14 or His97 that decreases glycolytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Each compound has different effects on TIMs, except on HsTIM, it is very important, because these compounds were chosen to not have a probable interaction with the HsTIM, which, we could verify in these in in vitro assays. All compounds were tested at a concentration of 175 μM, this concentration indicates that it has an acceptable value for drug development. The results in the enzymatic activity are indicated below at two hours of incubation for each TIM with the eight compounds (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we propose a potential site as a therapeutic target against the enzyme triosephosphate isomerase for drug development, and that this potential new drug could be safe to be used at humans. We determined the K in position 214 (near the sequence YGGSV−K214) is indispensable for the interaction with the tested compounds and it helps the interaction in the active site from TIM.…”
Section: Introductionmentioning
confidence: 99%
“…The glycolysis pathway, despite being present in all organisms, some of its enzymes have been proposed as targets for drug design [16][17][18], because the sequence and structure of proteins differ between species. In this pathway, triosaphosphate isomerase (TPI; E.C.…”
Section: Introductionmentioning
confidence: 99%
“…The main function of the TPI enzyme is to catalyze the interconversion of dihydroxyacetone phosphate into (D)-glyceraldehyde-3-phosphate; this process allows the two three-carbon molecules to continue being processed in the glycolytic pathway, since, without this reaction, there would be no net ATP production generated by the pathway [19]. Due to the relevance of this enzyme, some researchers have proposed the TPI as a potential target for the search (or synthesis) for new drugs [15][16][17][18], and even propose it as targets for the development of vaccines, of parasites that affect humans [16,20,21]. According to the aforementioned, it was in our interest to study the TPI of the fungus identified as F. oxysporum, since, despite being a pathogenic fungus of plants and/or humans, the analysis of biochemical characterization of this or another enzyme of the glycolysis had not been performed previously.…”
Section: Introductionmentioning
confidence: 99%